South East Europe gas markets: Reconfiguring supply flows and replacing Russian gas - Julian Bowden (The Oxford Institute for Energy Studies, 2022)
For many years Russian domination of SE Europe's gas imports meant it was regarded as 'Russia's market'. In the last 3 years, however, much new infrastructure has been commissioned, which has enabled the region to diversify its import mix and significantly change its gas flow patterns. TAP brings in Azeri pipeline gas, start-up of Croatia LNG and higher utilisation of Greece's Revithoussa has brought more LNG to the region, and opening of the Greece-Bulgaria interconnector has improved onward gas distribution. Turk Stream start-up has also opened potential opportunity for the now empty Trans Balkan pipeline system to be utilised for different gas flows. The purpose of this paper is to describe these infrastructure developments and consequent changes to gas supply flow patterns, and to assess what further change there might be as other planned infrastructure projects are completed over the next 5 years. There is also the Black Sea upstream, with Romania's Neptun deep awaiting FID and Turkey's Sakarya field about to produce its first gas in 2023, both of which can add new gas to the supply picture. The central question is whether, as a result of these investments, the region can have a non-Russian gas supply future. The conclusion is that sufficient capacity is almost in place to import and distribute enough alternative volume to replace the Russian imports - assuming of course that this other supply is available and at an acceptable price. There are other emerging possibilities also: there will be pricing and hub evolution implications from the greater interconnectivity and supply diversity; Greece can emerge as the LNG gateway for the region; a stronger sense of region should position it better for the net zero campaign, where the first priority must be the removal of lignite from SE Europe's energy mix.
Keywords: 330; Croatia LNG; Greece LNG; Greece-Bulgaria (ICGB) interconnector; LNG; Romania upstream; Russia; SE Europe gas supply; TAP; Turk Stream; Turkey upstream